Direct Displacement-based Seismic Design of Glulam Frames with Buckling Restrained Braces. Issue 8 (11th June 2023) - Dong, Wenchen; Li, Minghao; Sullivan, Timothy; MacRae, Gregory; Lee, Chin-Long; Chang, Theodore
ABSTRACT: This paper presents a direct displacement-based design (DDBD) approach for the buckling restrained braces (BRBs) braced glue-laminated timber (glulam) frame (BRBGF) structures. First, the critical design parameters of the DDBD approach were derived for BRBGFs. Then, using experimentally verified numerical models, pushover analyses and nonlinear time-history analyses (NLTHAs) were conducted on a series of one-storey BRBGFs to calibrate the stiffness adjustment factor λ for BRB-timber connections and the spectral displacement reduction factor η . Finally, the DDBD approach was verified as a prospective approach for the seismic design of multi-storey BRBGF buildings by NLTHAs of the case study buildings.